Ecological Reclamation of Lawn Coverings in Disturbed Areas. Issue 4 (March 2021) - Avdeeva, E; Zheltobryukhova, E
Abstract: Today, the problem of reclamation of landfills for solid domestic waste is urgent, which is a complex of works aimed at restoring the economic value and productivity of the restored territories. Ecological reclamation is a set of measures for the ecological and economic restoration of lands, the fertility of which has been disturbed as a result of human activity. The purpose of reclamation is to improve environmental conditions, restore the productivity of disturbed lands. In the city of Krasnoyarsk and its suburbs, the peculiarities of weather conditions are traced, affecting the growth and development of lawn coverings. In the course of the study of the correspondence of the parameters of climatic environmental factors to the criteria for the growth of high-quality lawn coverings for the reclamation of landfills, it was established that the humidity regime is the limiting factor. On the basis of this, we have developed types of trash mixtures for reclamation of disturbed areas. When arranging lawn coverings in the city of Krasnoyarsk and its suburban area, it is necessary to focus on the natural conditions of lawn moistening and adopt care technologies adequate to the prevailing conditions. the biological properties presented in these herbal mixtures of herbs meet the requirements that are imposed on the reclamation of disturbed areas and their care. They have high winter hardiness and drought resistance, resist pathogens, pests and weeds.